The Sino‐Nasal Outcome Test–22 as a tool to identify chronic rhinosinusitis in adults with cystic fibrosis. Issue 12 (30th July 2015) - Habib, Al‐Rahim R.; Quon, Bradley S.; Buxton, Jane A.; Alsaleh, Saad; Singer, Joel; Manji, Jamil; Wicox, Pearce G.; Javer, Amin R.
Abstract : Background: Chronic rhinosinusitis (CRS) is becoming increasingly prevalent in adults with cystic fibrosis (CF), as the median age of survival rises for these individuals. Delayed identification of CRS may contribute to worsening health‐related quality of life and increased treatment burden. Our objective was to investigate the utility of the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) as a tool to identify CRS in adults with CF. Methods: In this cross‐sectional study, participants were sampled from an adult‐specific CF clinic in Vancouver, Canada, between September 2013 and April 2014. CRS was determined by use of standardized diagnostic guidelines. Participants completed the SNOT‐22 and medical charts were reviewed for additional predictor variables. Logistic regression was used to compare the SNOT‐22 as a univariable predictor variable to a multivariable prediction model, in order to best differentiate CRS and non‐CRS participants. Results: Ninety‐three of 101 adults provided written informed consent. The prevalence of CRS was 56.3% (95% confidence interval [CI], 45.9% to 66.3%). Individuals with CRS reported significantly higher SNOT‐22 scores than non‐CRS participants (mean difference: 13.9; 95% CI, 6.1 to 21.7). The optimal SNOT‐22 score to differentiate CRS was 21 out of 110 (sensitivity: 76%, specificity: 61%, positive predictive value: 71%, likelihood ratio: 1.9). Conclusion: Compared to the current diagnostic gold standard, SNOT‐22 scores greater than 21 sufficiently identified adults with CF presenting with concomitant CRS. The SNOT‐22 is a simple instrument that can easily be implemented in adult CF clinics to assist care providers identify individuals requiring more detailed assessment or referral to a sinus clinic.